Upaya Peningkatan Konsumsi Protein Hewani Asal Ternak di Indonesia - Santoso, Urip (BPFP Universitas Bengkulu, 2022)
The literature review aims to discuss the energy and protein adequacy rate in Indonesia. The results of the study shows that the protein consumption of the Indonesian population per capita per day in 2020 was 61.98 g. Of the 61.98 g protein consumption, 8.43 g came from marine products such as fish, shrimp, squid and shellfish, 4.05 g from meat and 3.47 g from eggs and milk. Thus, the consumption of animal protein originating from livestock in Indonesia was on average 7.52 g per capita per day. Efforts to increase consumption of animal protein from livestock can be done by increasing awareness of nutrition as well as community income and community business efficiency. Efforts to increase consumption is the responsibility of not only the government but also all members of society. It could be concluded that increasing consumption of animal protein from livestock needs to be carried out intensively by the government and the community. Key words: consumption of protein from livestock, nutrition awareness, community income, nutrition campaign ABSTRAK Telaah pustaka ini bertujuan untuk membahas angka kecukupan energi dan protein di Provinsi Bengkulu. Hasil telaah menunjukkan bahwa konsumsi protein penduduk Indonesia per kapita per hari pada tahun 2020 adalah sebanyak 61,98 g. Dari 61,98 g konsumsi protein, 8,43 g berasal dari produk laut seperti ikan, udang, cumi dan kerang, 4,05 g dari daging dan 3,47 g dari telur dan susu. Jadi konsumsi protein hewani asal ternak penduduk Indonesia rata-rata sebesar 7,52 g per kapita per hari. Upaya peningkatan konsumsi protein hewani asal ternak dapat dilakukan dengan cara meningkatkan kesadaran gizi sekaligus pendapatan masyarakat serta efisiensi usaha masyarakat. Upaya peningkatan konsumsi ini merupakan tanggungjawab bukan saja pemerintah tetapi juga semua anggota masyarakat. Dapat disimpulkan bahwa peningkatan konsumsi protein hewani asal ternak perlu dilakukan intensif oleh pemerintah dan masyarakat.